2013
DOI: 10.2355/isijinternational.53.1401
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Inclusions in Low Carbon Al-Killed Steel during Ladle Furnace Refining and Calcium Treatment

Abstract: A plant trial of the productions of LCAK steel was performed, and characteristics of inclusions during LF refining and calcium treatment were investigated. Besides, thermodynamic diagram among magnesium, aluminum, and oxygen as well as calcium, magnesium, aluminum, and oxygen in the steel melt were studied to understand the fundamentals of inclusion modification by calcium treatment in LCAK steel. Furthermore, the change mechanisms of oxide inclusions and the precipitation of calcium sulfide were discussed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 172 publications
(133 citation statements)
references
References 27 publications
5
112
1
7
Order By: Relevance
“…16) In the following, the condition for the inclusion change of Al 2 O 3 →CaO-Al 2 O 3 is proposed by comparing the previous studies. 7,8,12,[15][16][17][18] The Ca contents were compared to estimate the condition because it was very difficult to compare the activities of Ca because their experimental situations were very different from each other. Some were for carbon steels and tool steels, while some were for stainless steels.…”
Section: Composition Evolution During Lf Refining Processmentioning
confidence: 99%
See 3 more Smart Citations
“…16) In the following, the condition for the inclusion change of Al 2 O 3 →CaO-Al 2 O 3 is proposed by comparing the previous studies. 7,8,12,[15][16][17][18] The Ca contents were compared to estimate the condition because it was very difficult to compare the activities of Ca because their experimental situations were very different from each other. Some were for carbon steels and tool steels, while some were for stainless steels.…”
Section: Composition Evolution During Lf Refining Processmentioning
confidence: 99%
“…It was reported that both MgO·Al 2 O 3 and the CaO-Al 2 O 3 system inclusions were detected in the refining stages of Al-killed steels. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] According to the report, MgO·Al 2 O 3 inclusions have the potential to cause nozzle clogging due to its high sinterability because they are stable with a solid state at the steelmaking temperatures.…”
Section: Factors To Determine Inclusion Compositions In Molten Steel mentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14][15][16][17]23,24) A large number of thermodynamic models based on thermodynamic and phase equilibrium data for a given system has been developed, 25) which can be used to predict the relationship between compositions of slag, steel, and inclusions in relatively simple systems, such as Al-O, [26][27][28] AlMg-O, [29][30][31] Al-Ca-O, [32][33][34] Al-Ti-O, [35][36][37] Al-Si-Ca-O, 38,39) Al-Si-Mn-O, [40][41][42] etc. However, the thermodynamic models can hardly be applied to a multicomponent system due to complicated calculations and lack of thermodynamic data.…”
Section: Introductionmentioning
confidence: 99%